IoT and Machine Learning based Smart Agri -Farming System - Shaik Mohammed Rafi, B. V. Chandra Sekhar, P. Anjaiah (International Journal of Modern Agriculture, 2021)
In the topical age of competition and risks in markets, advancements in technology are a must for better feasibility and growth. In the same way, it applies to the agriculture industry. Based upon their yield and quantity every farmer experience high spikes on the crop. At present, maintenance of farm is a very hot issue that needs to be apparatus at utmost propriety by rising water issues and proper methodologies. Automation of farms is proposed in this research. The suggested solution is based on the Internet Of Things(IoT), which would be an inexpensive and more accurate solution to farm needs. The main purpose of the monitoring system is to solve over-irrigation, crop-specific irrigation and soil erosion problems will be evolved to ease and efficiently manage all the irrigation problem. The main well-known fact in agriculture is water scarcity and over wastage of essential resources should be reduced. The proposed solution will be developed by the setup of Wireless Sensor Network(WSN) so that every farmer will be getting some sensor modules that will be transmitting data on the common server. These scenarios will be supported by Machine Learning(ML) algorithms based on the prediction for irrigation patterns. So such a comfortable approach to irrigation is provided in this paper.